ANALYSIS OF PRODUCTION INPUT EFFECT ON THE PRODUCTION OF CONNECTED CASSAVA FARMING BUSINESS - Muhammad Thamrin; Desi Novita; Muklis Hardianto (AGRIUM: Jurnal Ilmu Pertanian, 2015)
The aim of this study was to identify the influences of production inputs (land, seed, fertilizer solid, liquid fertilizers, herbicides, and labor) to the continued production of cassava farming and to identify the level of income from farming cassava farmers in Silau Rakyat Village Sei Rampah Resort Serdang Bedagai. Sampling method using census method which takes all the population. The data analysis method used is the multiple linear regression analysis and analysis of revenues. The results showed that the use of production inputs in the study area simultaneously affecting cassava production continued. While partially affecting cassava production is continued land, seeds and liquid fertilizer, while not affecting cassava production is continued solid fertilizers, herbicides and labor. Then based on the results of the analysis of the level of income is known that the level of income of farmers in the study area is high. Keyword : production inputs, farming